The impact of leadership and human resource management system on compliance through the implementation of strategic business process management - Suharmiko Suharmiko; Riani Rachmawati (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
Compliance is a useful factor in carrying out a business strategy that has implications for achieving company goals optimally and securing the company from various fatal deviations and negligence involving material and financial losses. The purpose of this study was to determine the role and impact of leaders together with HR professionals who are part of the human resource management system in creating compliance behavior and attitudes towards the implementation of strategic business process management. This research was conducted at PT PLN (Persero) as a public company but must achieve a lot of profit related to regulations, laws, customers, and society. And this study measures managers at the middle and lower levels spread across the territory of Indonesia quantitatively by analysis using Structural Equation Modeling and with the acquisition of 356 respondents. The results show that leadership and HR System Strength positively influence compliance intentions. Besides, these two variables are mediated by strategic Business Process Management have a positive influence on compliance intentions. So, in conclusion, Organizational Leadership, HRM system strength, and strategic Business Process Management are essential in increasing employee compliance intentions. Still, the interesting finding is the HR leaders and professionals should not pay too much attention and rely on strategic BPM in increasing compliance intentions because the results can reduce compliance attitudes and behavior.